State estimation for discrete-time switched positive T–S fuzzy systems under dwell time constraint. (August 2021) - Xu, Xiaozeng; Li, Yang; Zhang, Hongbin; Chen, Wei; Zheng, Qunxian
Abstract: This brief article is devoted to the design of a positive observer of the discrete-time switched positive Takagi–Sugeno (T–S) fuzzy systems (DSPFSs) under minimum or range dwell time constraints. The observer design for DSPFSs is considered both with the measurable premise variable and with the unmeasurable premise variable. First, convex sufficient conditions on the existence of observers for DSPLSs with the measurable premise variable are presented. Then, based on the above results, convex sufficient conditions on the existence of ℓ 1 positive observer for DSPFSs with the unmeasurable premise variable are derived. These conditions are presented in terms of linear programming. At last, some numerical examples of DSPFSs are given for illustration.